Chapter 9 Politics of (non)belonging enacting imaginaries of affected publics through forensic genetic technologies - Amelung, Nina (Taylor & Francis, 2022)
"Based on the premise that the project of Western Modernity is a structuring element of our societies, Racism and Racial Surveillance explores in detail its legacies of coloniality and racialization that interfere in a subtle and perverse way in the current social, cultural and political systems. Guided by an interdisciplinary methodology, the various contributions privilege historical contexts of colonial formation and offer a thorough and intersectional analysis on the specters of coloniality in the upsurge of racism, surveillance, and criminalization, as well as the presence of the phantom of the race in spaces of knowledge production such as that of artistic field, forensic genetics and criminal identification. Drawing on multi case studies the book then proffers key concepts and historical background that will be of interest to researchers, students and professionals in a broad range of areas of social sciences and humanities research, including fields such as criminology and policing, science and technology studies, arts studies, literary studies, race and ethnic studies and, finally, memory studies."